Comprehensive Molecular Analyses of an SLC Family-Based Model in Stomach Adenocarcinoma - Tao Yu; Shao-kun Yu; Kai-hua Lu (Pathology and Oncology Research, 2022)
Background: Solute carrier (SLC) family members are crucial in transporting amino acids across membranes. Amino acids are indispensable for both cancer and immune cells. However, the clinical significance of amino acid transporting SLC members in stomach adenocarcinoma (STAD) remains unclear. This study aimed to develop an SLC family-based model to predict the prognosis and the response of STAD patients to immunotherapy.Methods: A total of 1239 tumor cases were obtained from online databases. The training set (n = 371) consisted of RNA sequencing profiles obtained from The Cancer Genome Atlas (TCGA), while those from Gene Expression Omnibus (GEO) were used as the test set. Subsequently, the clinical characteristics and immune profiles were investigated, and potential immunotherapy response prediction values of the model were assessed.Results: Based on the TCGA cohort, an SLC family-based model was developed using multivariate Cox analysis. All tumor cases were stratified into high- and low-risk groups considering the SLC model. High-risk patients had a worse overall survival (OS) than low-risk patients, consistent with the results of GEO cohorts. Comprehensive analyses revealed that the high-risk group was correlated with aggressiveness-related pathways, whereas the low-risk group had better T helper cell infiltration and stronger immunotherapy response. Compared to the high-risk group, the low-risk group presented increased PD-L1 and tumor mutation burden.Conclusion: This SLC family-based model has the potential to predict the prognosis and immunotherapy outcomes of STAD patients. The survival of patients in the low-risk group was greatly prolonged, and the patients may benefit more from immunotherapy.